January protests shutdown (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in Kazakhstan. Data sourced from OONI.
Censorship Incident ID: KZ-2022-0001. Severity: critical. Confidence: 90%